Enhanced mechanical properties of a nickel-based superalloy by regulating laves and δ phases via hot rolling deformation - Jianhui Wei; Yanghuanzi Li; Changchang Liu; Shengnan Ma; Ji Gu; Min Lu; Min Song (Journal of Materials Research and Technology)
This article investigated the precipitation behaviors of laves phase and δ phase, and the mechanical properties of a nickel-based superalloy. The results show that the bulk laves phase surrounded by the acicular δ phase formed at the grain boundaries in the as-homogenization heat treated alloy. After 20 % rolling deformation at 550 °C, the laves phase re-dissolved and the δ phase bent, resulting in a simultaneous increase of 67.9 %, 27.4 % and 60.7 % in the yield strength (YS), ultimate tensile strength (UTS) and ductility of the alloy, respectively. A favorable combination of mechanical properties was achieved, with the YS being 576 MPa, the UTS being 689 MPa and the elongation being 28.6 %. When 40 % rolling deformation was carried out at 750 °C, the YS and UTS of increase significantly to 1194 MPa and 1240 MPa, and an acceptable elongation of 8.3 % due to the fragmentation of the laves phase and the fracture of the δ phase. The relationship between the microstructural evolution and the mechanical properties of the alloy was discussed. These findings offer valuable insights into the microstructural control of the laves phase and δ phase in nickel-based superalloys, providing an effective strategy for optimizing the mechanical performance.